Decline in alien plant species turnover among geographically isolated mountains with ropeway corridors - Asuka Koyama; Chika Egawa; Munemitsu Akasaka (Global Ecology and Conservation)
Anthropogenic corridors facilitate alien invasions from low to high elevations in mountains. While native plant assemblages generally show a large elevational turnover to alpine species, alien plant assemblages at high elevations seem to consist of only generalist species with broad tolerances, resulting in a nested structure of lowlands. These may cause homogeneous alien plant assemblages even in geographically isolated higher elevations, thereby undermining the alpine flora uniqueness. We focused on ropeway corridors that may facilitate alien invasions up long elevational gradients from lowlands, and examined the followings on 14 mountains across Japan: Are alien plant assemblages at high elevations accessible by ropeways formed as a subset of lowland alien species? and Are alien plant assemblages homogeneous among isolated higher elevations? We analyzed species richness and spatial turnover of alien and native species at the lower and upper ends of ropeways, as well as the effects of geographical and climatic factors on the spatial turnover and alien species’ presence probability at upper ends. Alien species richness decreased with elevation, whereas native species richness did not. The degree of spatial turnover of alien species was lower than that of native species, especially at upper ends, and was not affected by coordinal distance, unlike native species. The alien species’ presence probability at the upper ends was influenced by that at the lower ends. Our results highlight that homogeneous alien plant assemblages are formed across isolated higher elevations with ropeways. Strengthening the management of lowland alien species pools is necessary to conserve mountain biodiversity.